An experimental investigation on the heat transfer performance of a liquid metal high-temperature oscillating heat pipe. (March 2020) - Ji, Yulong; Wu, Mengke; Feng, Yanmin; Yu, Chunrong; Chu, Lilin; Chang, Chao; Li, Yantao; Xiao, Xiu; Ma, Hongbin
Highlights: A liquid metal high temperature OHP (LMHOHP) was first developed. The LMHOHP that can function at a temperature of over 500 °C. The LMHOHP can transport heat of 3169 W and achieve a thermal resistance of 0.08 °C/W. Abstract: This paper introduces the development of a liquid metal high-temperature oscillating heat pipe (LMHOHP) that can function under high-temperature conditions (over 500 °C). The LMHOHP has six turns with a total height of 310 mm. The sodium-potassium alloy (potassium 78%) was used as the working fluid, and the 310S stainless steel tube with an inner diameter of 6 mm as the shell tube. The LMHOHP heat transfer performance was investigated experimentally with a filling ratio of 45% at different input powers. Experimental results show that the LMHOHP can effectively generate steady-state oscillating motions at a working temperature of over 500 °C. When the steady-state oscillating motions exist, the temperature difference and thermal resistance between the evaporator and condenser were reduced significantly. At a heat input of 3169 W, the LMHOHP presents a minimum thermal resistance of 0.08 °C/W. This LMHOHP provides a new approach to next-generation high-temperature cooling devices.